THU0561 Adalimumab in Patients with Active and Inactive, Non-Infectious Uveitis: Visual I and Visual II Trials. (15th July 2016) - Brézin, A.P.; Dick, A.D.; Jaffe, G.J.; Ohno, S.; Namba, K.; Goto, H.; Inomata, N.; Song, A.P.; Kron, M.; Camez, A.; Tari, S.; Nguyen, Q.D.
Abstract : Background: Uveitis causes an estimated 10–15% of cases of blindness in western countries and there is an unmet need for effective therapies for patients (pts) with non-infectious uveitis who are at risk for long-term side effects from chronic corticosteroid use. Objectives: To assess adalimumab (ADA) efficacy and safety in patients with active and inactive, non-infectious uveitis. Methods: Adults with non-infectious intermediate, posterior, or panuveitis were enrolled in two global phase 3, double-masked trials, VISUAL I (pts with active uveitis despite ≥2 weeks (wks) of prednisone (PS), 10–60 mg/d) and VISUAL II (pts with inactive disease dependent on 10–35 mg/d of PS, to maintain inactivity). Pts were randomized 1:1 to receive placebo (PBO) or ADA subcutaneously (80 mg wk 0, followed by 40 mg every other wk from wk 1 up to 80 wks). In VISUAL I, all pts received a PS burst followed by taper to 0 mg by wk 15. In VISUAL II, PS taper to 0 mg was mandatory by wk 19. Integrated data (main study and Japan sub-study) from VISUAL I and VISUAL II trials are reported. The primary endpoint was time to treatment failure (TF) at or after wk 6 for VISUAL I or at or after wk 2 for VISUAL II. Nine ranked secondary endpoints were assessed and adverse events (AEs) were monitored. Results: The intent-to-treat (ITT) analyses included 233 (217 main study, 16 Japan sub-study) and 258 (226 main study, 32 Japan sub-study) pts from VISUAL I and VISUAL II, respectively (VISUAL I and VISUAL II: female: 58% and 61%; mean age, 43.2 years (y) and 43.1 y; mean duration of uveitis, 46 months (mt) and 59 mt). Risk of TF was reduced by 44% (VISUAL I) and 48% (VISUAL II) in ADA-treated pts compared to PBO group (VISUAL I: HR=0.56, 95% CI, 0.40–0.76, P <0.001; VISUAL II: HR=0.52, 95% CI, 0.37–0.74, P <0.001). Median time to TF was 3 mt for PBO, 4.8 mt for ADA (VISUAL I) and 5.6 mt for PBO, not estimable for ADA (>18 mt, as more than half of the pts did not achieve TF by wk 80; VISUAL II). ADA-treated pts had fewer TF criteria than PBO in both studies and treatment effects were numerically in favor of ADA for most of the secondary efficacy variables (Table ). ADA and PBO AE rates were similar (VISUAL I: 1063 vs 960 events/100 pt-y, VISUAL II: 854 vs 884 events/100 pt-y) in both studies, respectively. Conclusions: ADA lowered the risk of uveitic flare or visual acuity loss in pts with active and inactive disease when off PS. The safety profile was consistent with the known safety profile across the approved ADA indications. Acknowledgement: AbbVie funded the studies (VISUAL I [NCT01138657 ] and VISUAL II [NCT01124838 ]). All authors contributed to the development of the content. The authors and AbbVie reviewed and approved the abstract. The authors maintained control over the final content. Medical writing assistance was provided by Gaurav Patki, PhD of AbbVie Inc. Disclosure of Interest: A. P. Brézin Consultant for: AbbVie, A. D. Dick Consultant for: AbbVie, G. J. Jaffe Consultant for: AbbVie, S. Ohno Employee of: AbbVie, Santen, K. Namba Consultant for: AbbVie, H. Goto Consultant for: AbbVie, N. Inomata Shareholder of: AbbVie, Employee of: AbbVie, A. P. Song Shareholder of: AbbVie, Employee of: AbbVie, M. Kron Shareholder of: AbbVie, Employee of: AbbVie, A. Camez Shareholder of: AbbVie, Employee of: AbbVie, S. Tari Shareholder of: AbbVie, Employee of: AbbVie, Q. D. Nguyen Consultant for: AbbVie, Santen, XOMA, Bausch & Lomb